SMACKING TO INCREASE PRODUCTIVITY: CHANGING THE NARRATIVES OF ASNAF ENTREPRENEURS FROM MYJANA 2023 PROJECT - Suib, Fatin Husna; Mohamad Diah, Nurazzura; Harun, Ahmad Fahmi; Ahmad Suki, Amirah (IIUM Journal of Case Studies in Management, 2024)
The MyJANA 2023 Project is an innovative endeavor designed to uplift financially underprivileged Asnaf entrepreneurs in Perlis, Malaysia, through comprehensive training in entrepreneurship and digital marketing. Addressing systemic barriers, it seeks to foster economic independence and self-reliance among participants using the SMACK approach—centering on Self-motivation, Measurability, Assessment, Culture, and Knowledge. This methodology incorporates training on social media marketing, branding, and AI tools for business enhancement. The project has significantly improved entrepreneurial skills, business productivity, financial empowerment, and digital marketing proficiency, contributing to individual and broader social-economic upliftment. Aligned with the Sustainable Development Goals (SDGs), particularly SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), and SDG 10 (Reduced Inequalities), the initiative demonstrates the transformative power of targeted educational programs. Despite challenges like digital transition resistance and skills gaps, it has showcased the importance of adaptability, inclusivity, and continuous support. Looking forward, MyJANA 2023 aims to scale its model and enhance learning experiences through technology. It stands as a testament to the impact of education and entrepreneurship on transforming lives, laying a foundation for empowering disadvantaged communities.